Structure Of Treatment of Diseases of The Oral Mucosa and Periodontal Under the Influence of Covid 19 - Giyazova M.M. (Genius Publishing Group, 2021)
COVID-19 infection can be an individual while oral pathology. The new SARS-CoV-2 coronavirus is characterized by high contagiousness, transmitted by airborne droplets, directly through inhalation drops or indirectly through the use of infected objects. The survival rate of the virus on surfaces, depending on its composition, varies from 4 hours to 9 days. Initiation of infection is possible through binding of viruses to the host cell site in connection with the affinity receptor and an angiotensin converting enzyme (ACE2) distributed in the epithelium, alveoli, ascular endothelium, lung pneumocytes and masrophage.
Keywords: Oral Pathology; Survival Rate; endothelium; transmitted